2002
DOI: 10.2151/jmsj.80.1339
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Topography and Daytime Cloud Activity around Tibetan Plateau.

Abstract: The relationship between topography and daytime cloud activity over the Tibetan Plateau and surrounding areas was examined by using Geostationary Meteorological Satellite (GMS) Visible (VIS) and Infrared (IR) images during the premonsoon, and monsoon periods in 1998. Previous studies using IR images have already confirmed the strong diurnal variation of convective activity over the Tibetan Plateau. This study relies primarily on VIS images to analyze daytime cloud distribution because VIS images are more adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
66
2
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 19 publications
10
66
2
3
Order By: Relevance
“…Zonally elongated regions of high CCF are found near 28.5°N and 30.2°N, close to major mountain ranges C and D. High clouds are suppressed over valley B at 29.3°N. The CCF distribution is consistent with that shown by Kurosaki and Kimura (2002). At 21 LST (Fig.…”
Section: Characteristics Of Diurnal Variations In Convection and Precsupporting
confidence: 75%
See 1 more Smart Citation
“…Zonally elongated regions of high CCF are found near 28.5°N and 30.2°N, close to major mountain ranges C and D. High clouds are suppressed over valley B at 29.3°N. The CCF distribution is consistent with that shown by Kurosaki and Kimura (2002). At 21 LST (Fig.…”
Section: Characteristics Of Diurnal Variations In Convection and Precsupporting
confidence: 75%
“…Ueno (1998) showed that satellite-estimated precipitation is more likely to be over the major mountain ranges during the day (06 18 LST at 90°E) and over major valleys at night (18 06 LST). Kurosaki and Kimura (2002) used Geostationary Meteorological Satellite (GMS) visible and infrared data for both pre-monsoon and monsoon periods in 1998 to show that daytime (09 15 LST) clouds prevail over major mountain ranges of the TP. Such variations could be related to thermally induced local circulations driven by the topography of the TP.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkable diurnal variation in convection occurs over the plateau during the summer (e.g., Murakami 1983;Nitta and Sekine 1994;Yanai and Li 1994;Fujinami and Yasunari 2001). The convection depends strongly on thermallydriven regional-scale circulations induced by plateau topography (Ueno 1998;Kuwagata et al 2001;Kurosaki and Kimura 2002). Nevertheless, few authors have investigated convective variability on submonthly timescales over the Tibetan Plateau.…”
Section: Introductionmentioning
confidence: 99%
“…The temporal resolution is 3 h (UTC 00, 03, 06, 09, 12,15,18,21) and the spatial resolution is 0.25 • × 0.25 • . The daily aggregated precipitation is obtained by summing all 8 sets of 3-h precipitation totals for a given day.…”
Section: Methodsmentioning
confidence: 99%